DEVIANT BEHAVIOR IN HIGH SCHOOL STUDENTS AND ITS PREVENTION - Sadikova Qizjibek Quralbay qizi; Dùysenbaeva Bibigùl Bekmurzaevna; Najimatdinova Gulnaz Muyatdinovna; Seytniyazova Peruza Bekpolat qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: this article provides information about the deviant behavior of high school students and its prevention.